Ventricular Tachycardia Storm Management in Acute Cardiac Care: Prompt response to life-threatening conditions - Lestari, Puspa; Anjarwani, Setyasih; Rohman, Mohammad Saifur; Rizal, Ardian (Heart Science Journal, 2023)
Background: Ventricular Tachycardia (VT) storm or electrical storm (ES) is defined as cardiac electrical instability and refers to the occurrence of three or more ventricular tachyarrhythmias (VT and or ventricular fibrillation (VF)) in a 24-hour period, or VT recurring soon (within five minutes) after termination of another VT episode, or sustained or no sustained VT with total ectopic beats greater than sinus beats in a 24-hour period. The frequency of VT storms varies on population. When ICDs are implanted for primary prevention (4 percent), it is lower than when they are implanted for secondary prevention (20 percent).Case Summary: We presented patient with Ventricular Tachycardia (VT) storm. A 63-year old woman was admitted to emergency room with chief complaint frequent episodes of palpitation. She was found to have monomorphic VT with unstable hemodynamic. Then she got cardioversion 100 Joule, continued with lidocaine drip and VT reverted to sinus rhythm. Patient admitted to cardiovascular care unit, but she had VT refractory. She got complete revascularization for coronary artery before, but the episodic of VT still occurred with cardiogenic shock (CS) and pulmonary edema. She got cardioversion, amiodarone iv and inotropes, then observed this patient at CVCU. After the condition stable, this patient was discharged and planned for ICD insertion at the next admission.Discussion: We discuss the various available treatment options for VT storm and practical challenges faced in management of hemodynamically unstable VT storm. Initial management involves identifying and correcting the underlying ischemia, electrolyte imbalances, or other inciting factors.